When Whites Riot: Writing Race and Violence in American and South African Cultures - Rachleff, Peter (Labour / Le Travail, 2003)
The article reviews the book, "When Whites Riot: Writing Race and Violence in American and South African Cultures," by Sheila Smith.
Keywords: BOOKS – Reviews; Nonfiction; Racism; SMITH; Sheila; WHEN Whites Riot: Writing Race & Violence in American & South African Cultures (Book)

The Current Crisis of the South African Labour Movement - Rachleff, Peter (Labour / Le Travail, 2001)
[The article focuses] on a particular conflict in South Africa — the strike this past winter of several thousand Volkswagen workers in Uitenhage, outside of Port Elizabeth, a region known as "the Detroit of South Africa" — and [places] it within the context of a worsening material situation for most South Africans and growing political contusion and tension within the ruling "Triple Alliance" of the African National Congress (ANC), the Confederation of South African Trade Unions (COSATU), and the South African Communist Party (SACP). At this moment, there is an intensifying struggle over privatization and restructuring, a pending battle between pubhc employees and the ANC-run state; and growing enmity between COSATU and the ANC, driven by dissent within COSATU affiliates, over these issues of privatization, the pay of public employees, and a call for the revisions of labour laws in place since 1994, These particular conflicts and the overall situation rest, of course, on South Africa's location within the global economy and the different ways that internal forces are responding to it. In examining these internal forces we can learn more about not only the challenges of economic globalization but also the prospects for challenging it. –From author's introduction

Organizing the Unemployed: Community and Union Activists in the Industrial Heartland - Rachleff, Peter (Labour / Le Travail, 1998)
The article reviews the book, "Organizing the Unemployed: Community and Union Activists in the Industrial Heartland," by James J. Lorence.

The Origins and Evolution of the Field of Industrial Relations in the United States - Rachleff, Peter (Labour / Le Travail, 1993)
The article reviews the book, "The Origins and Evolution of the Field of Industrial Relations in the United States," by Bruce E. Kaufman.

The Fragile Bridge: Paterson Silk Strike, 1913; A Tale of Three Cities: Labor Organization and Protest in Paterson, Passaic, and Lawrence, 1916-1921 - Rachleff, Peter (Labour / Le Travail, 1991)
The article reviews two books:"The Fragile Bridge: Paterson Silk Strike 1913," by Steve Golin, and "A Tale of Three Cities: Labor Organization and Protest in Paterson, Passaic, and Lawrence 1916-1921," by David J. Goldberg.
Keywords: BOOKS – Reviews; FRAGILE Bridge: Paterson Silk Strike 1913; The (Book); GOLDBERG; David J.; GOLIN; Steve; Nonfiction; TALE of Three Cities: Labor Organization & Protest in Paterson; Passaic & Lawrence 1916-1921; A (Book)

Beyond the Martyrs: A Social History of Chicago's Anarchists, 1870-1900 - Rachleff, Peter (Labour / Le Travail, 1990)
The article reviews the book "Beyond the Martyrs: A Social History of Chicago's Anarchists, 1870-1900," by Bruce C. Nelson.
Keywords: BEYOND the Martyrs: A Social History of Chicago's Anarchists; 1870-1900 (Book); NELSON; Bruce C.; 1951-2011; Nonfiction; REVIEWS; Social history; books

A Contest of Ideas: Capital, Politics, and Labor - Rachleff, Peter (Labour / Le Travail, 2014)
This article reviews the book, "A Contest of Ideas: Capital, Politics, and Labor," by Nelson Lichtenstein.